Chemical bonding analysis in boron clusters by means of localized orbitals according to the electron localization function topology - Oña, Ofelia Beatriz (2015)
A series of small planar boron clusters has extensively been studied in the past using different theoretical approximations, and their chemical bonding has been rationalized in terms of aromaticity, antiaromaticity and conflicting aromaticity. Here, we study these systems by means of our recently proposed orbital localization procedure based on the partitioning of the space according to the electron localization function (ELF) topology. The results are compared with those obtained from the adaptive natural density partitioning (AdNDP) method, which is a most extensively tested orbital localization procedure. Minor discrepancies have been found, especially in large clusters. In those cases, an alternative set of localized AdNDP orbitals recovered the representation obtained by ELF localization procedure. These results support the need for multicenter bonding incorporation into the localization models for rationalizing chemical bonding in atomic clusters. Additionally, the aromatic character of the clusters, when it is present, is adequately supported by the more classical treatment based on the ELF topological analysis.